HBM4EU Chromates Study: Urinary Metabolomics Study of Workers Exposed to Hexavalent Chromium - Kozłowska, Lucyna (2022)
The HBM4EU Chromates study team consists of: Kukka Aimonen1, Rob Anzion2, Radia Bousoumah3, Maurice van Dael2, Karen S. Galea4, Ivo Iavicoli5, Kate Jones6, Henriqueta Louro2, Sophie Ndaw7, Simo P. Porras1, Edna Riberio8, and Riitta Velin1 Statistical team consist of: Natalia Buławska9, Dominika Jurkiewicz9 Correspondent affiliations: 1 Finnish Institute of Occupational Health, 00250 Helsinki, Finland; 2 Human Genetics Department, National Institute of Health Dr. Ricardo Jorge (INSA), Toxicogenomics and Human Health (ToxOmics), NOVA Medical School, Universidade Nova de Lisboa, 1649-016 Lisbon, Portugal; 3 Comprehensive Health Research Center (CHRC), 1169-056, Lisbon, Portugal; 4 Institute of Occupational Medicine (IOM), Edinburgh EH14 4AP, UK; 5 Department of Public Health, University of Naples Federico II, 80131 Naples, Italy; 6 Health and Safety Executive (HSE), Harpur Hill, Buxton SK17 9JN, UK; 7 French National Research and Safety Institute, 54500, Vandoeuvre-les-Nancy, France; 8 Public Health Research Centre, NOVA National School of Public Health, Universidade NOVA de Lisbon, 1600-560 Lisbon, Portugal; 9 QSAR Lab Ltd., 80172 Gdansk, Poland.